Metaphorical Expression in John Clare's Poems: I Am, The Skylark, and Remembrances - Fauzi, Fadilah Nur; Wibowo, Hanafi (Universitas Nurul Jadid, 2024)
This study investigates “Metaphorical Expression in John Clare’s Poems: I Am, The Skylark and Remembrances.” The purpose of this study is to identify the types of metaphors in John Clare’s selected works. This research adopts a qualitative approach. Data collection involved accessing the texts of these poems through reliable online literary archives, articles, and books during the research period of May to July 2024. The researcher conducted a close reading of each poem to document metaphorical expressions, which were then classified into Structural, Orientational, or Ontological types based on Lakoff and Johnson’s framework. A total of 11 metaphors were identified: 4 Ontological (36.4%), 3 Structural (27.3%), and 4 Orientational (36.4%). The most frequently used type of metaphor was Ontological Metaphors and Orientational Metaphors, reflecting Clare’s technique of personifying abstract concepts like sorrow and memory. This study highlights Clare’s mastery of metaphor to explore themes of identity and nature, offering a detailed view of his poetic style.